On Quantum Programming Languages - Valiron, Benoît (2024)
This thesis (Habilitation à diriger des recherches) presents some of my research contributions since my Ph.D defense in 2008. I have had the chance to participate in the development of quantum programming languages since their early developments: the presentation aims to present my point of view on the evolution of the subject, my contributions, and the current research trends in the community. The target audience is a graduate student interested in pointers to the field of quantum programming languages.